2014
DOI: 10.1007/s00132-013-2252-4
|View full text |Cite
|
Sign up to set email alerts
|

Erratum zu: Magnetresonanztomographische Untersuchungen bei Problemen mit Metall-auf-Metall-Implantaten

Abstract: Grading the severity of soft tissue changes associated with metal-on-metal hip replacements: reliability of an MR grading system. Skeletal Radiol 40(3):303-307 90. Hart AJ, Sabah SA, Bandi AS et al (2011) Sensitivi ty and specificity of blood cobalt and chromium metal ions for predicting failure of metal-on-metal hip replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other studies have reported MRI-detected muscle atrophy around MoM hip articulations [44][45][46][47][48]. Berber et al [45] investigated 74 MoM hip arthroplasties, 51 implanted by a posterior approach, 21 by a lateral approach, and 2 unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported MRI-detected muscle atrophy around MoM hip articulations [44][45][46][47][48]. Berber et al [45] investigated 74 MoM hip arthroplasties, 51 implanted by a posterior approach, 21 by a lateral approach, and 2 unknown.…”
Section: Discussionmentioning
confidence: 99%
“…With metal-metal tribological pairings, the terms cyst, ALVAL (aseptic lymphocytic vasculitis-associated lesion) or ARMD (adverse reactions to metal debris) are used synonymously with pseudotumor. These cases usually involve elevated metal ions in serum [11,35]. The patients are usually below the age of 50 and have undergone joint replacement surgery with metal-metal tribological paring (e. g. surface replacement) [34].…”
Section: Pseudotumorsmentioning
confidence: 99%